On the Firmness Code Noising to the Statistical Analysis of the Observable Data of Repeated Repetition - V. M. Deundyak; J. V. Kosolapov (Моделирование и анализ информационных систем, 2015)
We investigate the firmness of code noising to the statistical analysis of the evesdropped messages of repeated repetition. We give a structural description of the model of secured data transmission and construct an information analytical model of the observer. The formula for computing amount of volume, necessary for distinguishing alternative hypothesis with given errors of first and second sorts by sample of codewords is obtained.